Robust immobilization of uranium using biogenic FeS with lignocellulose from green plant waste - Wu, Ruoyan; Wang, Xiaolin; He, Siyu; Wu, Minyi; Li, Panyu; Show, Pau Loke; Han, Ping; Hamzah, Muhammad Hazwan; Zhang, Yongkui; Chen, Jing (Elsevier B.V., 2025)
The efficient immobilization of uranium from uranium-mine wastewater holds immense significance for the sustainable development of nuclear energy and environmental protection. However, traditional uranium separation methods face challenges including limited adsorption capacity, high operational costs and a significant risk of secondary pollution. In this study, a novel biogenic FeS composite material (Bio-LC-FeS) was synthesized with the incorporation of lignocellulose from green plant waste. Compared with other reported adsorption materials, this composite demonstrated superior uranium immobilization capability. Under the optimal conditions, theoretical immobilization capacity achieved as high as 1366.46 mg (U) g−1 (FeS addition) with an immobilization efficiency of 97.10 ± 0.44 %. More importantly, the immobilization rate of U(VI) by Bio-LC-FeS still reached as high as 92.13 ± 0.53 % with the simulation of actual acid leaching wastewater from uranium mine, demonstrating excellently environmental adaptability. This study revealed a synergistic mechanism of adsorption and reduction by Bio-LC-FeS for robust immobilization of U(VI) through a unique “LC-O-Fe(II)/S(-II)” composite adsorption layer and a “dual electron donor” system. Life cycle assessment and life cycle cost analysis validated the environmental and economic feasibility of this approach, indicating that the cost of uranium immobilization by Bio-LC-FeS was considerably lower compared to that of most alternative materials. This research provides a highly promising strategy for achieving efficient and robust uranium immobilization, as well as for developing environmentally friendly and economically viable solution.